Hubungan Kepemimpinan Situasional, Disiplin Kerja, dan Komitmen Organisasional Terhadap Kinerja Guru SD Gugus IV Kecamatan Buleleng - N. Santika; I.G.K.A Sunu; K.R. Dantes (Jurnal Administrasi Pendidikan Indonesia, 2021)
The problem in this study is whether there is a relationship between situational leadership, work discipline, and organizational commitment to the performance of teachers in Elementary School Group IV, Buleleng District. The purpose of this study was to determine the magnitude of the relationship of situational leadership, work discipline, and organizational commitment to the performance of teachers in Elementary School Cluster IV Buleleng District. This study is an "ex-post facto" study with a large sample of 59 people. Data collected by questionnaire and document. Data analysis was performed using simple regression techniques, multiple regression, and partial correlation. The results showed that: 1) there was a significant relationship between situational leadership and the performance of elementary school teachers in Group IV, Buleleng District, with a correlation coefficient of 0.651 and an effective contribution of 28.18%. 2) there is a significant relationship between work discipline on the performance of teachers in Elementary School Group IV, Buleleng District. with a correlation coefficient of 0.534 and an effective contribution of 13.08%. 3) there is a significant relationship between organizational commitment to the performance of teachers in Elementary School Cluster IV, Buleleng District, with a correlation coefficient of 0.520 and an effective contribution of 11.74%. 4) together, there is a significant relationship between situational leadership, work discipline, and organizational commitment to the performance of teachers in Elementary School Cluster IV, Buleleng District, with a dual correlation coefficient of 0.728 and its contribution of 53% to the performance of Elementary School Cluster IV teachers in Buleleng District. It can be concluded that there is a significant relationship between situational leadership, work discipline, and organizational commitment to the performance of elementary school teachers in Cluster IV Buleleng District.